2004
DOI: 10.1016/j.orthres.2003.11.011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tibiofemoral joint kinematics on patellofemoral contact pressures under simulated muscle loads

Abstract: Altered patellofemoral joint contact pressures are thought to contribute to patellofemoral joint symptoms. However, little is known about the relationship between tibiofemoral joint kinematics and patellofemoral joint contact pressures. The objective of this paper was to investigate the effect of tibiofemordl joint kinematics on patellofemoral joint pressures using an established in vitro robotic testing experimental setup. Eight cadaveric knee specimens were tested at 0", 30", 60°, 90", and 120" of flexion un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(116 citation statements)
references
References 31 publications
7
106
1
2
Order By: Relevance
“…Firstly, MRI knee kinematic data have shown that during the weight-bearing squat the femur moves and rotates underneath a relatively stationary patella, and that excessive femoral rotation may increase patellofemoral joint stress on the contralateral patellar facets. 10,18,24 Unfortunately, there are no MRI knee kinematic data for performing the lunge. Therefore, it is unknown how much femoral rotation occurs during the lunge and how this rotation varies among healthy individuals and those with pathologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, MRI knee kinematic data have shown that during the weight-bearing squat the femur moves and rotates underneath a relatively stationary patella, and that excessive femoral rotation may increase patellofemoral joint stress on the contralateral patellar facets. 10,18,24 Unfortunately, there are no MRI knee kinematic data for performing the lunge. Therefore, it is unknown how much femoral rotation occurs during the lunge and how this rotation varies among healthy individuals and those with pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Cadaveric data have demonstrated that increased hamstring activity results in posterior translation of the leg relative to the thigh; for any given knee angle, this effect may result in a decrease in the angle formed between the quadriceps force vector and the patellar tendon force vector, increasing patellofemoral joint force and stress. 18 Unfortunately, the effect of hamstrings force on posterior leg translation is currently unknown.…”
mentioning
confidence: 99%
“…There is increasing evidence that proximal factors may be associated with the pathogenesis of PFP.Biomechanical studies have shown that excessive femoral internal rotation in weight bearing leads to increased lateral patellar tracking, reduction in patellofemoral contact area (Besier et al, 2008;Huberti and Hayes, 1984;Lee et al, 2003;Li et al, 2004;Salsich and Perman, 2007) and increased lateral patellofemoral joint stress (Souza et al, 2010). This is proposed to lead to change in the patellofemoral joint articular cartilage, overloading the subchondral bone, causing pain .…”
Section: Introductionmentioning
confidence: 99%
“…The use of a robot arm overcomes these issues [11,12]. In this case, the hip is fixed and the distal tibia is rigidly attached to a robot arm, controlling all six DOF.…”
Section: Introductionmentioning
confidence: 99%